Resistant cultivars, fungicides combat downy mildew of spinach - Koike, Steven T.; Smith, Richard; Schulbach, Kurt F. (California Agriculture, 1992)
The recent outbreak of spinach downy mildew, caused by a new race of the pathogen, left California growers without resistant cultivars and with few chemical controls. However, two fungicides have proved effective against the pathogen and two new resistant cultivars are now commercially available on a limited basis.